Book Reviews - Hui, Baisali; Sarkar, Dhrubajyoti (Multicultural Shakespeare: Translation, Appropriation and Performance, 2016)
Cefalu, Paul. Tragic Cognition in Shakespeare’s Othello: Beyond the Neural Sublime. London and New York: Bloomsbury, 2015. Pp. viii + 124. ISBN: 978-1-4725-2346-4 Ryan, Kiernan. Shakespeare’s Universality. Here’s Fine Revolution. Bloomsbury Arden Shakespeare. London and New York: Bloomsbury, 2015. Pp. xvi, 141. ISBN: PB-978-1-4081-8349-6. Price not stated